THE ROLE AND FUNCTIONS OF THE HONOR BOARD IN HANDLING CASES OF ALLEGED VIOLATIONS OF THE CODE OF CONDUCT MEMBERS OF THE DPRD KAB. GOWA IN THE PERSPECTIVE OF SIYASAH SYAR'IYYAH - Taufiq Hidayah D,; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
Indonesia a state of law as stated in Article 1 Paragraph (3) of the Constitution. This affirmation becomes the basis for administration of government. The 1945 Constitution Article 1 Paragraph (3) states that the State of Indonesia a state of law as a basis for the exercise of state power to realize a clean, authoritative government, free from KKN, and the realization of checks and balances. The main problem in this study is the role and function of the honorary body in handling cases of alleged violations of the code of ethics of members of the DPRD Kab. Gowa in the perspective of siyasa syar'iyyah. This type of research is field research using qualitative methods with the research approach used is syar'i normative theology and social politics. Based on the results of this study indicate that in enforcing the code of ethics, the Honorary Board performs 2 ways, namely prevention and prosecution. Prevention is carried out by providing education for board members, in the form of socialization, training and or other means determined by the Honorary Board. Through the prevention system, it is hoped that DPRD members can understand and comply with the rules and code of ethics. Meanwhile, the prosecution was carried out by referring to the DPRD's rules and regulations, but since 2019-2022 the Honorary Body has never received reports of violations of the code of ethics by members of the DPRD.